Global Viral Hepatitis Strategy: Issues with Hepatitis B Immunization in India - Pathni, Anupam Khungar; Pathni, Rajiv (Indian Journal of Community Health, 2017)
Hepatitis B vaccination, a key component of the recently adopted Global Viral Hepatitis Strategy, has been plagued by various issues since its introduction under the National immunization program in India. While the concerns relating to the inclusion of the vaccine under the Universal Immunization Program, the vaccination strategies adopted and prevention of mother to child transmission of hepatitis B have been largely resolved, data from recent research has underscored the need for regular monitoring of immunological and epidemiological outcomes of the vaccine. Controversies surrounding the safety and efficacy of the recently introduced combination pentavalent vaccine have highlighted that besides reinforcing surveillance of adverse events following immunization in the public sector, the private health sector in the country needs to be supported in this activity by increasing awareness and strengthening public-private collaboration